Nonagenários criadores - Degani, Marcia (2012)
This study talks about the creative artistic creation by non professional elder artists who reached 90 years old. Those elders, only due to their advanced age, are generally put aside in reason of doubts about their lucidity and capacity of production. Thus, it is possible to affirm that the interviewed persons of this job resisted to the social conception of oldness, especially those who are over eighty years old. For the reflection of these persons and their work it was necessary to investigate the meaning of being old in the society of nowadays, the nature of the artistic production and the exercise of creation. The direct contact with the interviewed elderly and their work afforded to enter in their universe, their subjectiviness and the particular way they find to deal with the reality of oldness. This study proposes to show the individuality of well successful oldness based on creative activities